Baseline Characteristics and Risk Factors of Pulmonary Arterial Hypertension in Systemic Lupus Erythematosus Patients. Issue 10 (March 2016) - Huang, Can; Li, Mengtao; Liu, Yongtai; Wang, Qian; Guo, Xiaoxiao; Zhao, Jiuliang; Lai, Jinzhi; Tian, Zhuang; Zhao, Yan; Zeng, Xiaofeng
Abstract : Abstract: Peking Union Medical College Hospital (PUMCH) has started a single-center right heart catheterization (RHC)-based pulmonary arterial hypertension (PAH) study in systemic lupus erythematosus (SLE) since 2006. The baseline characteristics of these patients were described and the risk factor for PAH in lupus was identified. The demographic, clinical, laboratory, and treatment characteristics of SLE patients with PAH when they were registered were collected as the baseline data. A case-control study was conducted by taking the admitted SLE-non-PAH patients adjusted for age and gender in a 4:1 ratio during the same period as the controls. The associated variables were examined by binary multivariate logistic regression analysis to identify possible risk factors. A total of 111 RHC-confirmed SLE-PAH patients were enrolled, with the onset age of 34.6 ± 8.6 years old and the average SLE duration of 5 years. RHC revealed mPAP as 46.4 ± 11.4 mm Hg, CI as 2.7 ± 0.8 L/min × m 2, and PVR as 10.5 ± 4.8 WU. 46% of patients were WHO Fc I–II. All patients were treated with immunosuppressive agents and 65% patients had PAH-targeted therapy. The case-control study had confirmed 2 independent risk factors previously published: pericardial effusion (OR = 21.290, P < 0.001) and anti-RNP antibody (OR = 12.399, P < 0.001). Meanwhile, 6 independent variables were discovered: baseline SLE duration (OR = 1.118, P = 0.007), interstitial lung disease (OR = 17.027, P < 0.001=, without acute rash (OR = 3.258, P = 0.019), anti-SSA antibody (OR = 4.836, P = 0.004), SLEDAI⩽9 (OR = 26.426, P < 0.001), ESR⩽20 mm/h (OR = 12.068, P < 0.001), and uric acid > 357 μmol/L (OR = 9.666, P < 0.001) to be associated with PAH in SLE patients. The PUMCH study has shown that SLE patients complicated with PAH are usually earlier diagnosed and have less disease severity than patients without PAH. The immunosuppressive therapy rate and the PAH target therapy rate were high, which is consistent with reports from Western countries. This study has confirmed that pericardial effusion and positive anti-RNP antibody are risk factors for SLE-associated PAH. Long SLE disease duration, the presence of interstitial lung disease, without acute skin rash, positive anti-SSA antibody, low SLEDAI and ESR, and high uric acid levels are also associated with PAH in SLE patients.